Histological Study of The Cerebellum In Adult Quail Coturnix coturnix (Linnaeus, 1858) - B.AbidÂ , Asmaa; A. Al-Bakri, Nahla (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A histological study was conducted to examine the structure of Cerebellum in Coturnix coturnix (Linnaeus). The results showed that the cerebellum is a portion of the Rhombencephalon and Metencephalon lying behind the cerebrum, the surface of the cerebellum contains deep folds and appears spherical in its shape. It represented the dorsal side of metencephalon and surrounded the roof of IV ventricle.          The cerebellum consists of three parts spino cerebellum, cerebro cerebelluum and vestibulo cerebellum; and three lobes anterior lobe, posterior lobe and flocculonodular lobe. The corpus cerebellum (Vermis) consists of nine folds called cerebellar-folia (IX-I) and separated from each other by sulci.  Histologically, the cerebellum consists of  a cerebellar cortex that is called gray matter composed of three major layers, outer molecular layer, middle Purkinje cells layer and inner granular layer, the second region of cerebellum is called medulla which is called white matter.